The Effectiveness of Miracle Questions on Students' Rational Problem-Solving Skill - Budi Astuti; Rizqi Lestari (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2018)
The aim of the study was to discover the effectiveness of miracle questions technique on rational problem-solving skill. The method employed in the study was pre-experimental with single-subject experimental design. The subject of the study was five managers of HIMA PPB FIP UNY consisting of three males and two females. The present study was conducted in 3 (three) phases namely pre-treatment, treatment, and post-treatment. The data were collected using problem-solving scale and miracle questions technique counseling guide. The data were analyzed using non-parametric statistical analysis namely wilcoxon test. The result of the study exhibited that miracle questions technique was effective on rational problem-solving skill (Asymp sig. (2-tailed 0,043<0,05) With 5% of level of significance. Therefore, miracle questions technique is effective to improve the rational problem-solving skill of the student organizer of HIMA PPB FIP UNY. The result of the study can be used as consideration to applying miracle questions technique in broader scope for counselor.